Plasmonic Nanostructure for Enhanced Light Absorption in Ultrathin Silicon Solar Cells. (5th November 2012) - He, Jinna; Fan, Chunzhen; Wang, Junqiao; Cheng, Yongguang; Ding, Pei; Liang, Erjun
Abstract : The performances of thin film solar cells are considerably limited by the low light absorption. Plasmonic nanostructures have been introduced in the thin film solar cells as a possible solution around this issue in recent years. Here, we propose a solar cell design, in which an ultrathin Si film covered by a periodic array of Ag strips is placed on a metallic nanograting substrate. The simulation results demonstrate that the designed structure gives rise to 170% light absorption enhancement over the full solar spectrum with respect to the bared Si thin film. The excited multiple resonant modes, including optical waveguide modes within the Si layer, localized surface plasmon resonance (LSPR) of Ag stripes, and surface plasmon polaritons (SPP) arising from the bottom grating, and the coupling effect between LSPR and SPP modes through an optimization of the array periods are considered to contribute to the significant absorption enhancement. This plasmonic solar cell design paves a promising way to increase light absorption for thin film solar cell applications.